2002
DOI: 10.1073/pnas.042667999
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of Vibrio cholerae : Genes that correlate with cholera endemic and pandemic disease

Abstract: Historically, the first six recorded cholera pandemics occurred between 1817 and 1923 and were caused by Vibrio cholerae O1 serogroup strains of the classical biotype. Although strains of the El Tor biotype caused sporadic infections and cholera epidemics as early as 1910, it was not until 1961 that this biotype emerged to cause the 7th pandemic, eventually resulting in the global elimination of classical biotype strains as a cause of disease. The completed genome sequence of 7th pandemic El Tor O1 strain N169… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
376
1
10

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 423 publications
(399 citation statements)
references
References 34 publications
12
376
1
10
Order By: Relevance
“…Total RNA was treated with DNase I (Ambion, Austin, TX). Genomic DNA (gDNA) was labeled with Cy5 or Cy3-dCTP (Perkin-Elmer Life Sciences), as described (10). RNA was reverse-transcribed to produce fluorescently labeled cDNA (11).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total RNA was treated with DNase I (Ambion, Austin, TX). Genomic DNA (gDNA) was labeled with Cy5 or Cy3-dCTP (Perkin-Elmer Life Sciences), as described (10). RNA was reverse-transcribed to produce fluorescently labeled cDNA (11).…”
Section: Methodsmentioning
confidence: 99%
“…We recently constructed a genomic V. cholerae microarray that we used in comparative genomics (10) and to expression profile regulatory mutants affected in quorum sensing and virulence (11). More recently, Merrell et al (12) reported microarray transcriptional profiling of bacteria shed in the stools of cholera patients.…”
mentioning
confidence: 99%
“…The presence of genes responsible for motility-conferring flagella and sensing of the environment supports the assumption of a freeliving stage for the Osedax symbionts. The large number of mcp genes identified in the symbionts may reflect complex associations with other organisms, as observed for many pathogens and some symbionts (B20-40 mcp genes is common; Dziejman et al, 2002;Robidart et al, 2008). However, the free-living relative Neptunomonas japonica also possesses a large number of mcp copies (n ¼ 17), thus it is more likely that this reflects an increased need for detection and response to dissolved organic matter at abyssal depths, as has been observed in the genomes of many deep-sea bacterial species (Lauro and Bartlett, 2008).…”
Section: Evidence For a Free-living Lifestagementioning
confidence: 99%
“…Of more than 200 O serogroups of V. cholerae, epidemics of cholera were caused by V. cholerae serogroup O1 until 1992. V. cholerae O1 has two biological variants or designated biotypes, namely Classical (CL) and El Tor (ET), which differ from each other in both phenotypic and genetic characteristics, as well as by the type of cholera toxin (CT) that they harbour (Dziejman et al, 2002;Kaper et al, 1995;Olsvik et al, 1993). In addition, the two biotypes differ in terms of infection patterns of disease; for example, the CL biotype strains cause more severe disease, while ET strains are more efficient in host-to-host transmission than their CL counterparts.…”
Section: Introductionmentioning
confidence: 99%